Jokowi’s Second Cabinet Reshuffle: Implications for Indonesian Politics - Arifianto, Alexander Raymond (2016)
Indonesian President Joko Widodo (Jokowi) has just reshuffled his cabinet for the second time in a year, replacing a number of allegedly troubled ministers, but also some reform-minded professionals.